Metastatic Small Cell Carcinoma of the Urinary Bladder That Recurred in the Vagina 6 Years after Radical Cystectomy: A Case Report - Makoto Isono; Keiichi Ito; Shinsuke Hamada; Masahiro Takahashi; Hidenori Sasa; Hideyuki Shimazaki; Tomohiko Asano (Case Reports in Urology)
Small cell carcinoma (SCC) of the urinary bladder is highly aggressive and portends a poor outcome. Herein, we report a patient with recurrent SCC of the urinary bladder who experienced an unusually long-term disease-free duration after radical cystectomy. The patient was a 60-year-old woman who had undergone transurethral resection followed by radical cystectomy for muscle-invasive bladder cancer (high-grade urothelial carcinoma with adenocarcinomatous differentiation) 6 years prior; the surgical specimen had a negative surgical margin. She was referred to our hospital because of continuous bleeding from her vagina. Magnetic resonance imaging showed a mass located at the anterior wall of her residual vagina, a biopsy of which confirmed a pathological diagnosis of adenocarcinoma. The vaginal tumor and a section of the sigmoid colon were resected en bloc and were pathologically diagnosed as adenocarcinoma and SCC. We reevaluated the initial transurethral resection specimen and found SCC with foci of adenocarcinoma concomitant with high-grade urothelial carcinoma. Local recurrence and metastasis at the pelvic bone occurred 4 months later; although radiation therapy was performed, she died of the progressive disease.